Про властивість балансування командних ролей на протязі виконання проекту - Сулімова, Юлія Євгенівна; Любченко, Віра Вікторівна (НТУ "ХПІ", 2016)
Побудована модель переходів між командними ролями на основі ланцюга Маркова. Виконано моделювання переходів між командними ролями на протязі виконання проектів дизайну, проектів реалізації та комбінованих проектів. Зроблено висновок про природність балансування командних ролей за рахунок переходу деяких членів команди до вторинних ролей.

Belbin’s research explained that a full complement of the team roles is the best chance for a team’s success. So one of important task for a project manager is a balance of team members based on Belbin roles. We developed the model of team role changing during the software project development. To do it we built a model of team role changing based on discrete Markov chain and parametrize it based on Self-Perception Inventory and experts evaluation. Developed model provides the possibility to simulate team role changing during the downright design, downright implementation and variety projects. It is concluded that the natural behavior of team members is to amend the primary role to secondary one to achieve the balance in the team.
About team roles balancing during project execution
Keywords: командні ролі Белбіна; ланцюг Маркова; анкета самосприйняття; експертне оцінювання; Belbin team roles; team roles balancing; Markov chain; Self-Perception Inventory; expert evaluation